2022
DOI: 10.1371/journal.pone.0278761
|View full text |Cite
|
Sign up to set email alerts
|

Health motivations and perceived barriers are determinants of self-care behaviour for the prevention of hypertension in a Malaysian community

Abstract: Introduction Self-care behaviour is fundamental in preventing hypertension in the general population. According to the Health Belief Model, health beliefs and perceptions influence the success in adopting disease prevention strategies. While factors influencing hypertension self-care behaviour have been examined previously in patient populations, they have not been assessed in the general community. Methods This was a cross-sectional study conducted between 12 June 2020 to 26 July 2021. An online survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…Consistent evidence from studies has supported the beneficial effects of exercise and physical activity on blood pressure control for the prevention of hypertension. Maintaining a healthy diet especially in reducing salt and calorie intake, regular physical activities and blood pressure checks need to be improved in the community (Tan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent evidence from studies has supported the beneficial effects of exercise and physical activity on blood pressure control for the prevention of hypertension. Maintaining a healthy diet especially in reducing salt and calorie intake, regular physical activities and blood pressure checks need to be improved in the community (Tan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to lifestyle interventions presents a particular challenge for future programs (Pinho et al, 2021), while Ried Larsen et al (2019 highlighted the need for "further studies on maintaining lifestyle changes." Adherence is defined as "…the extent to which a person's behavior-taking medication, following a diet, and/or implementing lifestyle changes-aligns with agreed recommendations from a healthcare provider…" (Paulter et al, 2020: p.2) Tan et al (2022) found that health-related motivations are determinants of self-care behavior for the prevention of hypertension in a Malaysian community. Korkiakangas et al (2011) suggested that adults with T2D experienced many meaningful motivators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding the demographic PA profile of these student teachers, particularly in the context of Demographic Transition Theory, is critical (Zaidi & Morgan, (2017). It remains unclear how the demographic factors of student teachers at ODL institutions in Kuala Lumpur influence their PA behaviours and patterns (Tan et al, 2022). While the Health Belief Model (HBM) suggests that perceptions about health and beliefs about outcomes influence health behaviours (Saghafi-Asl et al, 2020), there is limited empirical evidence on how PA student teachers' levels differ across demographic groups such as gender, age and socioeconomic status (Pedersen et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%